2012
DOI: 10.5012/bkcs.2012.33.5.1485
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Immunoassay for Detecting Hippuric Acid Based on the Interaction of Osmium-Antigen Conjugate Films with Antibody on Screen Printed Carbon Electrodes

Abstract: An electrochemical immunoassay based on osmium-hippuric acid (HA) conjugate films onto the electrode is presented for the detection of urinary HA. This is the first report on the use of the oxidative electropolymerization of 5-amino-1,10-phenanthroline (5-NH 2 -phen) for immobilizing an antigen, osmium-conjugated HA. As a redox mediator, [Os(5-amino-1,10-phenanthroline) 2 (4-aminomethylpyridine-HA)Cl] +/2+ (Os-phen-HA) was successfully synthesized and electropolymerized onto the screen-printed carbon electrode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…10,11 In this paper, a facile synthetic process enabling the direct coordination of pyridyl-N to pentacyanoferrate for the detection of small organic molecules is reported. 12,13 In particular, two novel strategies are employed to design the homogeneous electrochemical immunoassay system, as follows: First, the synthesized complex between pyridyl-N and pentacyanoferrate was not only an excellent electroactive molecule, but also provided direct conjugation to the antibody for the detection of the target molecules.…”
Section: -4mentioning
confidence: 99%
“…10,11 In this paper, a facile synthetic process enabling the direct coordination of pyridyl-N to pentacyanoferrate for the detection of small organic molecules is reported. 12,13 In particular, two novel strategies are employed to design the homogeneous electrochemical immunoassay system, as follows: First, the synthesized complex between pyridyl-N and pentacyanoferrate was not only an excellent electroactive molecule, but also provided direct conjugation to the antibody for the detection of the target molecules.…”
Section: -4mentioning
confidence: 99%
“…Electrochemical immunoassays can be divided into homogeneous and heterogeneous methods, depending on whether the antibody or antigen needs to be immobilized on the electrode or not. Most reported electrochemical immunoassays have used heterogeneous methods, which usually display higher sensitivity and less interference [ 28 , 29 , 30 ], however, it has been reported that the physical adsorption and covalent conjugation methods used for antibody immobilization on a solid surface can cause random orientation, denaturation, and steric hindrance in the antibodies. The latter reduces the specificity and reproducibility during the immunoassays [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to our previous papers, the benefits of the present paper include (1) the easy immobilization of Ni ions onto the electrode; (2) the prompt synthesis of ferrate antigen; (3) less interference due to the electrostatic interaction between Ni(II) and ferrate; and (4) a relatively low cost [ 29 31 ]. In this study, we used electrochemical techniques to form organic films containing imidazole rings on the electrodes ( Figure 1 (1)).…”
Section: Introductionmentioning
confidence: 99%